EPM Inventory Practices - Chandren, Sitraselvi; Nadarajan, Santhirasegaran (2022)
Mr Tim is a Certified Optometrist with 15 years of work experience in the optical industry. He has been working with EPM for more than 5 years. As the Manager of EPM, he oversees the outlet operations by directing optical services, managing inventories and repairing and adjusting eyewear. Mr Tim is aware of the competitive nature of the eyewear industry. An effective inventory management will be a good solution to attain competitive advantage to outperform its competitors particularly for small medium enterprises. The inventory practices are evaluated from the point of inventory arrival to the outlets until it is sold to customers. The inventory practices should be evaluated based on inventory recording, planning (holding level, reorder level and safety stock), software system and safety measures. Thus, Mr Tim had to prioritize the evaluation of the current inventory practices as inventory management is crucial for the EPM business profitability. This is an evaluation case. This case is suitable for Inventory Management, Production & Operation Management and Financial Accounting subjects.